Four-Rooted Mandibular First Molar with an Unusual Developmental Root Fusion Line: A Case Report - Jojo Kottoor; Denzil Valerian Albuquerque; Natanasabapathy Velmurugan; Mylswamy Sumitha (Case Reports in Dentistry)
The paper describes the anatomical variation of four roots in a mandibular permanent first molar diagnosed using multiple angulated preoperative radiographs and its successful nonsurgical endodontic management. Careful observation and exploration of the pulpal floor using a dental operating microscope revealed a peculiar developmental root fusion line on the pulp chamber floor. Based on the above observation, a correlation between this unusual line and the existence of additional roots has been proposed and discussed.